The National Cultural Dimensions of Lithuania - Mockaitis, Audra I. (Ekonomika, 2002)
This paper introduces the results of national cultural dimensions of potential Lithuanian managers, according to Hofstede’s indices. It will be seen that Lithuanians scored high on Masculinity, and average on Uncertainty Avoidance, Individualism and Power Distance, relative to all other countries in the database. These results are discussed in terms of their likely influence on management and marketing in Lithuania.